2007
DOI: 10.1016/j.ejvs.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Ultrasound-guided Sclerotherapy for Varicose Veins: Medium-term Results Assessed by Ultrasound Surveillance

Abstract: Ultrasound-guided sclerotherapy gives satisfactory results if it is accepted that treatment may need to be repeated to achieve secondary success. Results provide a basis for further research to explore factors that might affect outcome. Younger patients with larger diameter saphenous veins may warrant alternative forms of treatment, particularly for small saphenous reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(132 citation statements)
references
References 21 publications
5
118
2
7
Order By: Relevance
“…Our outcome parameter are similar to those quoted in the literature [2][3][4][5][6] with negligible complication rates and high degree of initial success rates with 15 legs (89%) achieving complete closure with a single injection and all patients achieving closure with two injections.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our outcome parameter are similar to those quoted in the literature [2][3][4][5][6] with negligible complication rates and high degree of initial success rates with 15 legs (89%) achieving complete closure with a single injection and all patients achieving closure with two injections.…”
Section: Discussionsupporting
confidence: 73%
“…Ultrasound guided foam sclerotherapy is one such option it was introduced in 2001 by Tessari et al [1]. Foam sclerotherapy has been used with very low complication rates and with success rates up to 90% [2,3]. In this article we present our two needle technique of ultrasound guided foam sclerotherapy along with our short term results.…”
Section: Introductionmentioning
confidence: 98%
“…These results are comparable to those achieved with surgical or other interventional endovascular procedures. 7,[10][11][12][13][14][15][16][17][18][19] Our study consisted of a representative number of patients with uncomplicated VVs (59%) and severe venous insufficiency (41%) referred to a vascular outpatient clinic. We have demonstrated that the rate of complete and partial obliteration does not differ between these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Myers et al study [14] the only complication observed in this study was deep vein thrombosis which occurred in 3.2% of patients. This is somewhat higher than reported in other studies.…”
Section: Citationmentioning
confidence: 98%